2006
DOI: 10.1542/peds.2006-0961
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Parentally Reported Weight and Height for Preschool-Aged Children in Belgium and Its Impact on Classification Into Body Mass Index Categories

Abstract: Our results show the inaccuracy of parentally reported weight and height values in Belgium for classifying preschool-aged children into BMI categories. Therefore, accurate measurements of weight and height should be encouraged in studies in which BMI of children is a variable of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
71
3
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 17 publications
8
71
3
5
Order By: Relevance
“…Previous studies have consistently shown that, on average, weights are underestimated, heights are overestimated and the resultant BMIs are underestimated, although the correlations between self-reported and measured values are strongly high. [46][47][48] Thus, it is likely that the prevalence of overweight based on self-reported data in this study is underestimated, which might have diluted the present findings.…”
Section: Discussionmentioning
confidence: 59%
“…Previous studies have consistently shown that, on average, weights are underestimated, heights are overestimated and the resultant BMIs are underestimated, although the correlations between self-reported and measured values are strongly high. [46][47][48] Thus, it is likely that the prevalence of overweight based on self-reported data in this study is underestimated, which might have diluted the present findings.…”
Section: Discussionmentioning
confidence: 59%
“…Nevertheless, for most studies that make direct comparisons, the mean parent-reported child height and weight were close to the corresponding measured means, usually within Ϯ1 cm or Ϯ1 kg, [76][77][78][79][80] and reasonably represented by underestimates and overestimates of the measured means. There are, however, exceptions.…”
Section: Parent-reported Height Weight and Bmimentioning
confidence: 86%
“…These errors generally resulted from the under-reporting of height" (p. 8). Likewise, in their Belgian study, Huybrechts et al (2006) stipulate how substantial these biases can be: "Among all children requiring nutritional advice on the basis of being overweight or obese, more than one half of the overweight children and >75% of the obese children would be missed with the use of parentally reported weight and height values" (p. 2109).…”
Section: Methodsmentioning
confidence: 99%
“…There is considerable evidence that such self-reporting leads to large biases (e.g. Huybrechts et al, 2006;Shields et al, 2011). 6 Our paper, therefore, not only investigates the association between maternal employment and obesity but contributes to the existing literature by exploring the association between maternal work and meal patterns, diet and physical activity from a European perspective.…”
Section: Previous Researchmentioning
confidence: 99%